31 Racial Demographic Reporting in Clinical Trials Informing NCCN Kidney Cancer Guidelines - Suhail Sapkota; Niket Shah; Asish Nepal; Maha Bayya; Nadeen Saad; Shreya Motkur; Jason Law; Sai Sushrutha Vemula; James Hosner; Ling Wang; Daniel Isaac (The Oncologist, 2026)
Abstract Background Racial and ethnic disparities persist in kidney cancer incidence and outcomes, yet the evidence-based guiding treatment may not reflect the populations most affected. The American Cancer Society reports a higher burden among African American, American Indian, and Alaska Native populations. The National Comprehensive Cancer Network (NCCN) guidelines define standard-of-care management, but the representativeness of the clinical trials informing these recommendations remains unclear. We evaluated racial and ethnic reporting and participant composition in trials cited within NCCN kidney cancer guidelines. Methods We systematically reviewed 262 references cited in the National Comprehensive Cancer Network (NCCN) Kidney Cancer Guidelines (Version 3.2025). Clinical trials were included, while reviews, case reports, and non-clinical studies were excluded, resulting in 92 eligible studies. Studies were evaluated for reporting of racial demographics, participant racial composition, publication year, and geographic origin (U.S. vs international). Reporting rates were summarized descriptively. Temporal trends (2000–2024) were analyzed in five-year intervals using Fisher’s exact test, with subgroup comparisons between U.S. and international studies. Results Among 92 clinical trials, only 39 (42.4%) reported racial demographics. Reporting increased numerically from 20.0% (2000–2004) to 57.7% (2015–2019) but was not statistically significant (p = 0.277). U.S.-based studies reported race more frequently than international studies (72.5% vs 18.9%). Among trials reporting race, White participants comprised the majority (84.0%), with marked underrepresentation of Black (1.4%), Hispanic (0.8%), American Indian/Alaska Native (0.0%), and Native Hawaiian/Pacific Islander (0.0%) populations. Significant temporal variation was observed in White participant representation, with lower proportions in 2010–2014 and higher proportions in 2020–2024 (p < 0.0001). Conclusions Less than half of clinical trials informing the NCCN kidney cancer guidelines report racial demographics, with no meaningful improvement over time. Persistent underrepresentation of minority populations and inconsistent reporting, especially in international studies, undermine the generalizability of guideline-defining evidence. Mandating standardized racial and ethnic reporting in oncology trials is critical to advancing equitable cancer care.